Attention Problems Predict Risk of Violence and Rehabilitative Engagement in Mentally Disordered Offenders - Puzzo, Ignazio; Sedgwick, Ottilie; Kelly, Rachel; Greer, Ben; Kumari, Veena; Guðjónsson, Gisli; Young, Susan (Frontiers in Psychiatry, 2019)
Mentally disordered offenders (MDOs) endorse difficulties with attention, impulsivity, and hyperactivity. Assessing these difficulties among MDOs may confer practical benefits for the management and provision of care for this population, by informing strategies to improve rehabilitative engagement and risk assessments for violence. However, there is a dearth of literature exploring these cognitive problems in MDOs in relation to outcome factors. Forty-eight MDOs from a high-security hospital completed the QbTest, which measures the domains of inattention, impulsivity, and hyperactivity. Comprehensive file review of clinical and occupational/vocational rehabilitative engagement and Historical Clinical Risk Management-20 (HCR-20) were used as outcome measures of interest. Participants displayed greater cognitive deficits in attention, impulsivity, and hyperactivity compared to the general population. The domain of inattention and omission errors was related to occupational/vocational therapy engagement as well as a higher risk of present and future violence as measured by the HCR-20. The findings suggest that QbTest is a helpful objective tool that could be incorporated into the assessment of MDOs. Specifically, inattention emerged as a strong predictor of patients’ risk of violence as well as patient’s vocational therapy engagement. Therefore, cognitive skills programs targeting attention problems should be introduced to improve outcomes for this population.